1984
DOI: 10.1093/ajcp/82.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacteriuria by Leukocyte Esterase, Nitrite, and the Automicrobic System

Abstract: The predictive value for detection of significant bacteriuria was determined for use of the Chemstrip leukocyte esterase-nitrite dipstick (LN) and the Vitek Automicrobic System (AMS) using a conventional culture method (CM) as the reference procedure. The predictive values for positive and negative tests for detection of greater than or equal to 10(5) bacteria/mL for LN testing alone (2,782 specimens), AMS testing alone (729 specimens), and AMS testing of only LN positive specimens (253 specimens) were 29% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…The prevalence of infection in the elderly population ranges from 5 to 20% in men to 10 to 20% in women (100). Elderly patients with obstruction, poor bladder emptying, dementia, stroke, diabetes mellitus, and cardiovascular diseases are more likely to have bacteriuria than patients in the same age group without these abnormalities (100).…”
Section: :1mentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of infection in the elderly population ranges from 5 to 20% in men to 10 to 20% in women (100). Elderly patients with obstruction, poor bladder emptying, dementia, stroke, diabetes mellitus, and cardiovascular diseases are more likely to have bacteriuria than patients in the same age group without these abnormalities (100).…”
Section: :1mentioning
confidence: 99%
“…On the other hand, the most sensitive method (98%) for detecting i105 CFU/ml was the microscopic examination of stained centrifuged urine. However, this procedure is tedious and time-consuming because it requires centrifugation of 10 ml of urine for 5 (30). However, the specificity for each of the dipstick tests was 98%.…”
Section: Laboratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many screening methods have been proposed to detect bacteria in urine on the day of collection, both to shorten the delay inherent in the culture system and to decrease the time spent in the laboratory separating negative specimens from those considered to have significant bacteriuria. These screening tests include several manual (4,5,8,13,15,18), semiautomated (10,11,14), and automated systems (7,9,10,17).…”
mentioning
confidence: 99%
“…We set 5 × 10 4 CFU/mL as the discriminator value because it has been reported 8 that the strips can reliably detect fewer than 10 4 CFU/mL. Bartlett et al 9 have shown that there is a significant decrease in negative predictive value at less than 10 4 CFU/mL, and although Kass recommends 10 5 CFU/mL in a normal population, our population was not normal, but had a relatively high incidence of urinary tract infections. We felt that we could not ignore any culture greater than 5 × 10 4 CFU/mL.…”
Section: Discussionmentioning
confidence: 99%